(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2023)
Cadmium (Cd) in the waters considered as one of the pollutants that potentially pollute the waters and contaminating the aquatic biota. The heavy metal cadmium commonly comes from the industrial waste, agriculture, and also other human activities as found around the pond waters of Mangunharjo, Semarang. The purpose of this study was to analyze the cadmium content in sediment and water as well as the Blue swimming crabs (Portunus pelagicus) found in Mangunharjo pond waters. This research was held from December 2020 to January 2021. Measurement of Cadmium concentration was analyzed by the Atomic Absorption Spectrophotometer (AAS) method. The results showed the contamination of heavy metal Cadmium in water measured at <0.001-0.395 mg/l which has exceeded the quality standards for marine biota. The concentration of Cadmium in bottom sediments and blue swimming crab was measured at <0.001 mg/kg and 0.028-1.96 mg/kg. The Bio-concentration factor (BCF) was obtained between 60 - 1655 in December and 0.5 - 1014 in January, which categorized as low to very high. The concentration of cadmium in crab samples had exceeded the quality standard set in BPOM Regulation No. 23/2017, which has a maximum value of 0.1 mg/kg. The calculation of the maximum weekly intake of cadmium-contaminated crabs in this study is 0.0065 kg of meat/week for children weighing 15 kg and 0.21 kg of meat/week for adults weighing 50 kg. Aquatic environmental parameters such as temperature, pH, salinity and dissolved oxygen had various numbers between research stations and also between research periods. Crabs from Mangunharjo waters are contaminated with the heavy metal Cadmium, so it requires special attention to keep them safe for consumption.